Prevalence of menopausal symptoms and health-seeking behavior of school teachers with menopausal symptoms in Kumbakonam, South India - Sundararajan, Madhuvarshini; Srinivasan, Valarmathi (International Journal Of Community Medicine And Public Health, 2023)
Background: Menopausal transition shows symptoms that vary from one woman to another, it includes vasomotor symptoms, sexual symptoms, and psychological symptoms. A determination of the most common medical problem in this broad occupational group serves as the premise for actions that help teachers to preserve their health and their ability to work in their profession. Objectives of the study were to estimate the prevalence of menopausal symptoms among peri and post-menopausal school teachers in Kumbakonam and to determine the health-seeking behavior of school teachers with menopausal symptoms. Methods: A descriptive cross-sectional study was conducted among female teachers aged between 40-60 years in Kumbakonam. The random sampling technique was used, and a total of 264 teachers were included in the study. A semi-structured questionnaire was used to collect the sociodemographic details and the menopausal rating scale was used. Results: The mean (SD) age of the participants was 51.67 (4.9). 49.25% were peri-menopausal, 50.8% were post-menopausal. Among the reported symptoms of peri-menopausal, irritability (68.5%), physical and mental exhaustion (66.1%), and joint and muscular pain (66.2%) were predominant. In post-menopausal women, preponderant symptom was 73.9% suffers from joint and muscular pain followed by sleep problems (70.2%), physical and mental exhaustion (63.4%). 31.8% of menopausal women sought health care services. Conclusions: In this study it was found that 93.5% of menopausal women experienced atleast menopausal symptom. However, majority did not seek health care services. Implementing a health education could be a measure to enhance health-care seeking behavior. Improved awareness and access to healthcare services can improve proper health-seeking behavior.